STATISTICAL ANALYSIS OF FINANCIAL ACCOUNTS IN CASE OF NON-FINANCIAL CORPORATIONS - Ilyés, Csaba; Molnár, Emese Ilyés (European Scientific Journal, ESJ, 2014)
In the present economic conditionsit is more and more important for the macroeconomic analysts to usenew processesbased on theoretical and practical approaches which differ the present technics foranalysis andto make forecasts. In this paper we dealwith a new approach can be used toanalyse the financial instruments of non-financial companies. Ourresearchdoes not observe the income and consumption of the system of national accounts, but we focused on the financial accounts which are based on more reliable information. The purpose of our research was to analyse the financial accounts of non-financial corporations’ sector data. In this paper we analysed the financial accountsof Huusing statistical tools. We aimed to determine the potential regularities and regressions in the time series.